2017
DOI: 10.1007/s10803-016-2992-1
|View full text |Cite
|
Sign up to set email alerts
|

Social and Non-social Hazard Response in Drivers with Autism Spectrum Disorder

Abstract: Driving is a complex task that relies on manual, cognitive, visual and social skill. The social demands of driving may be challenging for individuals with Autism Spectrum Disorder (ASD) due to known social impairments. This study investigated how drivers with ASD respond to social (e.g., pedestrians) and non-social (e.g., vehicles) hazards in a driving simulator compared to typically developing drivers. Overall, participants responded faster to social hazards than non-social hazards. It was also found that dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Adults with ASD have also self-reported difficulties in "processing fast-moving visual events", a description that certainly applies to the complex and dynamic nature of the driving environment [45]. Further, the type of hazards drivers with ASD encounter may also affect the speed at which they react to and avoid them [46].…”
Section: Processing Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults with ASD have also self-reported difficulties in "processing fast-moving visual events", a description that certainly applies to the complex and dynamic nature of the driving environment [45]. Further, the type of hazards drivers with ASD encounter may also affect the speed at which they react to and avoid them [46].…”
Section: Processing Speedmentioning
confidence: 99%
“…Driving is a largely social task that requires interaction with other drivers and anticipation of other drivers' and road users' behavior to negotiate safely [101,102]. Very few studies have investigated the impact of these social impairments on driving performance in drivers with ASD [46,56] or ADHD [84].…”
Section: Important Gaps and Unanswered Research Questionsmentioning
confidence: 99%
“…Research has shown that people on the autism spectrum may experience executive function deficits [ 2 , 9 ], which will directly impact on their ability to develop driving skills and drive safely. Research investigating the driving behaviour of people on the autism spectrum found that they notice driving hazards but they displayed a delay in response to social hazards that required interactions with other road users, such as failing to give way to pedestrians who show clear intent to cross the road [ 12 14 ]. This is thought to be related to a combination of reduced processing of social stimuli and attention deficits, which is very problematic when learning to drive a motor vehicle—a process which requires collaborative problem-solving skills [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Static ROI, on the other hand, have a fixed position in the virtual environment (e.g., side-view mirrors, speedometer, and the navigation system). Social ROI consisted of pedestrians and cyclists, following the earlier designation by Sheppard et al (2010), which has also been adopted in recent related work (Bishop et al 2017; Sheppard et al 2017). …”
Section: Methodsmentioning
confidence: 99%